MO308COULD THE PRESENCE OF ANCAS IN IGA NEPHROPATHY WITH CRESCENTS HAVE A CLINICAL IMPLICATION?. (29th May 2021) - Castañeda Amado, Zaira; Gabaldon, Alejandra; Sanz, María Teresa; Bury, Roxana; Baldallo, Cinthia; Zuñiga, Jose; León, Juan Carlos; Sanchez, Cesar; Vergara, Ander; Bermejo, Sheila; Soler, María José; Seron Micas, Daniel; et al.
Abstract: Background and Aims: IgA nephropathy (IgAN) is the most common glomerulonephritis. The presence of ANCAs in this pathology represents a rare coincidence. However, it is not clear if the presence of IgA or IgG ANCAs in these patients could have clinical significance. We aim to describe the presence of IgA and IgG ANCAs in patients diagnosed with IgAN with crescents, and its possible clinical implications. Method: Retrospective study from 2013 to 2020, it included all patients diagnosed by kidney biopsy of IgAN with extracapillary proliferation. Outpatient follow-up time was up to 24 months. Demographics and clinicopathologic data, ANCAs subtype, characteristics of the biopsy and treatment at the time of diagnosis/follow up was recollected. Results: From 2013 to 2020, 17 adults were diagnosed with IgAN and extracapillary proliferation. 5 patients presented ANCAs, 3 (17%) were IgA ANCAs and 2 (11%) were IgG ANCAs. At diagnosis, the median age was 48 years old (27-75 years, sd. 15), with 9 women (52%). At the time of diagnosis, the most common clinical presentation was hypertension (71%). The laboratory analysis showed that median hemoglobin was 11.7 mg/dl (8.4-14.9 mg/dL, sd. 1.5), median creatinine was 2.2 mg/dL (0.55-5.7 mg/dL, sd. 1.4) and median proteinuria was 3.5 g/mgCr (0.1-12 g/mgCr, sd. 3.5). 7 patients (41%) presented extracapillary proliferation less than 25%, 7 patients presented it between 25% and 50%, and 3 patients (17%) had it in more than 50%. 5 (30%) patients presented fibrinoid necrosis. 1 (6%) patient needed renal replacement therapy upon admission. In terms of treatment, all patients with ANCAs IgAN received endovenous steroids and cyclophosphamide. The mean follow-up time was 6 months. Oral steroids (59%) and mycophenolate (41%) were the most frequent treatments. At six months, the median creatinine was 1.9 mg/dL (0.4-7, sd. 1.78) and the median proteinuria was 1.45 g/gCr (0.12-5.9, sd. 1.84 g/gCr). 3 patients developed end-stage chronic kidney disease and requiring substitute renal therapy; 4 patients died. Statistical analysis did not show differences in clinical characteristics, demographics, kidney function, proteinuria, need for renal therapy replacement or mortality according to the presence or subtype of ANCA. ANCA negative patients presented less than 25% of extracapillary proliferation in renal biopsy (p = 0.04). ANCA positive patients presented more fibrinoid necrosis than ANCA negative patients (p=0.01). Conclusion: Given the limited size of our sample, our results do not allow us to be conclusive, showing no significant differences between the ANCA subtypes. However, from the point of renal biopsy, it is observed that patients with negative ANCAs present less extracapillary proliferation; and that patients ANCA positive presented more fibrinoid necrosis.